The Global Debt Trap: How to Escape the Danger and Build a Fortune by Claus Vogt and Roland Leueschel - Haque, M Shamsul (Journal of Business and Technology (Dhaka), 2013)
DOI: http://dx.doi.org/10.3329/jbt.v7i2.16454 Journal of Business and Technology Vol.7(2) 2012: 57-61